Analysis of liquid spray structures using two-photon fluorescence laser sheet imaging - Ulrich, Hannah; Lehnert, Bastian; Guenot, Diego; Svendsen, Kristoffer; Lundh, Olle; Will, Stefan; Wensing, Michael; Berrocal, Edouard; Zigan, Lars (Vol 1 No 1 (2021): ICLASS Edinburgh 2021, 2021)
In this work two-photon laser-induced fluorescence (2p-LIF) laser sheet imaging is used to analyze the structure and the atomization behavior of water and ethanol sprays. Multiple light scattering is reduced by 2p-LIF measurements using a femtosecond laser. This allows high-contrast spray imaging close to the nozzle resulting in an improved identification of single liquid structures. A commercial 6-hole DISI (Direct-Injection Spark-Ignition) injector was studied at different injection pressures, operated with ethanol and water containing a LIF dye (fluorescein). Compared to water, the ethanol spray structure shows increased cone angles in the nozzle near-filed. For the size of the liquid structures, no clear dependency on the fluid properties is observed in this spray region.<br
Keywords: 2p-LIF; Spray; Atomization; Femtosecond